Alarm information association scheme of cloud resource pool based on big data analysis - Qing LI (Dianxin kexue)
An end-to-end intelligent operation and maintenance management system of cloud resource pool was studied,and a technical framework of intelligent obstacle detection module was proposed.The basic method of realizing end-to-end alarm association of cloud resource pool was analyzed.The realization of anomaly detection analysis method of single KPI and fault propagation chain analysis method of multi-KPI in cloud resource pool were expounded.The relationship between physical host alarm and virtual host alarm,IP SAN storage alarm and virtual object storage alarm,host device alarm and network alarm were introduced emphatically,which provide a reference for improving the end-to-end intelligent operation and maintenance capability of cloud resource pool.